2019
DOI: 10.1093/brain/awz115
|View full text |Cite
|
Sign up to set email alerts
|

MSH3 modifies somatic instability and disease severity in Huntington’s and myotonic dystrophy type 1

Abstract: The mismatch repair gene MSH3 has been implicated as a genetic modifier of the CAG·CTG repeat expansion disorders Huntington’s disease and myotonic dystrophy type 1. A recent Huntington’s disease genome-wide association study found rs557874766, an imputed single nucleotide polymorphism located within a polymorphic 9 bp tandem repeat in MSH3/DHFR, as the variant most significantly associated with progression in Huntington’s disease. Using Illumina sequencing in Huntington’s disease and myotonic dystrophy type 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
120
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(149 citation statements)
references
References 47 publications
(68 reference statements)
10
120
2
2
Order By: Relevance
“…Given the lack of experimental data, analysis of big data sets can address this question. Numerous genome-wide association studies have found that SNPs in the MLH1 and MSH3 genes act as genetic modifiers of HD's age of onset (128,130,(325)(326)(327)440). Likewise, an SNP in PMS2 modifies age of onset in several other poly(Q) diseases (441).…”
Section: Mmrmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the lack of experimental data, analysis of big data sets can address this question. Numerous genome-wide association studies have found that SNPs in the MLH1 and MSH3 genes act as genetic modifiers of HD's age of onset (128,130,(325)(326)(327)440). Likewise, an SNP in PMS2 modifies age of onset in several other poly(Q) diseases (441).…”
Section: Mmrmentioning
confidence: 99%
“…Likewise, an SNP in PMS2 modifies age of onset in several other poly(Q) diseases (441). Furthermore, an SNP in MSH3 affects the CTG repeat somatic instability level in DM1 patients (28,440).…”
Section: Mmrmentioning
confidence: 99%
“…The case of HDAC5 is possibly more complex as its partner, HDAC3, has been speculated to play a role in the deacetylation of MSH3 [32], which is a known modifier of repeat instability [32,55,[58][59][60][61][62][63][64][65][66][67]. The results obtained with PInT are concordant with a role for HDAC5 in trans, which may be that it helps control the deacetylation of MSH3 before it binds to the repeat tract.…”
Section: Discussionmentioning
confidence: 66%
“…In trinucleotide repeat mouse models, MSH3 expression is an important parameter in the degree of triplet instability and is considered as a limiting factor in this process [59,[63][64][65]. Recent data revealed that MSH3 single-nucleotide polymorphisms are associated with somatic mosaicism rates by potentially modifying MSH3 expression and/or activity in DM1 large cohorts [66,67]. In addition, genetic association analyses suggest that MSH3/DHFR three tandem repeat alleles, named 3a alleles, may reduce somatic rates but also delay the onset in DM1 patients [67].…”
Section: Dm1 Variability and Modifiersmentioning
confidence: 99%
“…Recent data revealed that MSH3 single-nucleotide polymorphisms are associated with somatic mosaicism rates by potentially modifying MSH3 expression and/or activity in DM1 large cohorts [66,67]. In addition, genetic association analyses suggest that MSH3/DHFR three tandem repeat alleles, named 3a alleles, may reduce somatic rates but also delay the onset in DM1 patients [67]. MSH3 is clearly a genetic modifier of somatic instability in DM1 but also in other CTG•CAG trinucleotide repeat diseases, suggesting a common mechanism [66,67].…”
Section: Dm1 Variability and Modifiersmentioning
confidence: 99%